2006
DOI: 10.1002/ajhb.20501
|View full text |Cite
|
Sign up to set email alerts
|

Mode of inheritance of dermatoglyphic pattern intensity index on fingers in five Indian populations: A comparative study between individual trait and its factor

Abstract: Our previous study (Karmakar et al. 2005 Ann. Hum. Biol. 32:445-468) was on 500 pedigrees of five different populations, with factor 1 comprising quantitative finger dermatoglyphics (including pattern intensity index, PII) and factor 1 controlled by major genes. The present results of a complex segregation analysis of the individual trait PII of the same five populations were compared with previous results to ascertain the extent of variation between individual trait PII and its factor (factor 1) with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Intra-familial correlation coefficients are greater for TFRC than for PII and I mp , i.e., in relations mother-child-0.470, 0.290 and 0.188, respectively (Sengupta and Karmakar, 2004), father-child-0.460, 0310 and 0.173 Karmakar, 2004), sib-sib-0.450, 0.310 and0.194, respectively (Sengupta andKarmakar, 2004). Similar values of the correlation coefficients for TRC: mother-child 0.333, father-child 0.406, sib-sib 0.291 and PII: mother-child 0.338, father-child 0.345, sib-sib 0.392 have been reported by and Karmakar et al (2006): mother-child 0.370, father-child 0.377, sib-sib 0.369 for PII-L and mother-child 0.358, father-child 0.356, sib-sib 0.369 for PII-R. Smallest correlations concerned then directional asymmetry (DA) and fluctuating asymmetry (FA) of complex of quantitative traits among others ridge counts: parent-offspring -0.033 (PC1 DA), 0.136 (PC1 FA), sib pairs-0.017 (PC1 DA), 0.129 (PC1 FA) (Karmakar et al, 2012b).…”
Section: Categories Of Parentssupporting
confidence: 76%
See 1 more Smart Citation
“…Intra-familial correlation coefficients are greater for TFRC than for PII and I mp , i.e., in relations mother-child-0.470, 0.290 and 0.188, respectively (Sengupta and Karmakar, 2004), father-child-0.460, 0310 and 0.173 Karmakar, 2004), sib-sib-0.450, 0.310 and0.194, respectively (Sengupta andKarmakar, 2004). Similar values of the correlation coefficients for TRC: mother-child 0.333, father-child 0.406, sib-sib 0.291 and PII: mother-child 0.338, father-child 0.345, sib-sib 0.392 have been reported by and Karmakar et al (2006): mother-child 0.370, father-child 0.377, sib-sib 0.369 for PII-L and mother-child 0.358, father-child 0.356, sib-sib 0.369 for PII-R. Smallest correlations concerned then directional asymmetry (DA) and fluctuating asymmetry (FA) of complex of quantitative traits among others ridge counts: parent-offspring -0.033 (PC1 DA), 0.136 (PC1 FA), sib pairs-0.017 (PC1 DA), 0.129 (PC1 FA) (Karmakar et al, 2012b).…”
Section: Categories Of Parentssupporting
confidence: 76%
“…DA is inherited mostly in dominant type and FA is additive (Karmakar et al, 2013); • PII-variability is influenced by the same genetic component representing a similar mode of inheritance with major gene involvement (Karmakar et al, 2006); • 18 quantitative finger and palmar dermatoglyphic traits (MZ/DZ) -significant proportion of additive genetic variance (93.5% to 72.9%); bivariate variance decomposition analysis -significant correlation in residual variance between digital pattern size factor versus finger pattern intensity factor, and palmar main lines factor versus a-b ridge count (Karmakar et al, 2011b); • finger and palmar quantitative traits, among them PII (MZ/DZ)-the additive genetic variance component was significant in both sexes for four traits: PII, AB RC, RC HB, and ATD L; the results of the bivariate variance decomposition analysis revealed that PII and RC HB have a significant correlation in both genetic and residual components (Karmakar et al, 2012a); • dermatoglyphic diversity -a little genetic effect obtained from familial correlations but no evidence of major gene contribution found to be involved; segregation analysis -despite the presence of significant inheritance (rejection of environmental model), the nature of inheritance is more complex, than Mendelian model ; • finger pattern (MZ/DZ)-the most parsimonious model shows twin resemblance in count of all three basic finger patterns on 10 fingers; it has significant dominant genetic variance component across all fingers. In the general model, the dominant genetic variance component proportion is similar for all fingertips (about 60%), and the sibling environmental variance is significantly nonzero, but the proportion between additive and dominant variance components was different; genetic model fitting technique of segregation analyses-dominant genetic variance component or a specific genetic system modifies the phenotypic expression of the fingertips patterns (Karmakar et al, 2011a,b);…”
Section: Categories Of Parentsmentioning
confidence: 99%
“…Significant sex differences (4.03) appear for total (TFRC) finger ridge counts, the main line A and D terminations, but there are no significant differences on the palmar a-b ridge count. Thus, compared to the finger ridge count, the results of palmar traits Karmakar et al 2002Karmakar et al , 2006Karmakar et al , 2007Karmakar et al , 2010. This difference between palm and finger may be due to the possible role of the environmental (prenatal) factors in the realization of the dermatoglyphic sex difference.…”
Section: Palmar Dermatoglyphicsmentioning
confidence: 99%
“…Traditional dermatoglyphic methods have not yet demonstrated a consistent relationship of fingerprints to the early gestational environment. Whereas the sum of RCs on all 10 fingers might be influenced by polygenic inheritance (Holt, 1961;Karmakar et al, 2006;Weninger et al, 1976;Young et al, 1981), other aspects of integumentary patterning may be under epigenetic control (Jiang et al, 2004). Contrasts between groups of digits have been described as evidence for developmental fields that possibly reflect the prenatal environment (Jantz and Hawkinson, 1979;Siervogel et al, 1979).…”
mentioning
confidence: 99%